Advances in injectable self-healing biomedical hydrogels. (May 2019) - Tu, Yujie; Chen, Nuan; Li, Chuping; Liu, Haiqian; Zhu, Rong; Chen, Shengfeng; Xiao, Qiao; Liu, Jianghui; Ramakrishna, Seeram; He, Liumin
Graphical abstract: Abstract: In recent years, implantable biomaterials have attracted significant interest owing to their potentials for use in the therapy of physical defects and traumas. Among the implantable biomaterials, hydrogels have received increasing attention for their tunable structures and good rheological behavior. However, the mechanical failures of traditional gel materials during normal operation remain a serious issue. To overcome this problem, hydrogel materials with self-healing and injectable abilities have been developed, with their potential for autonomous self-recovery and minimally invasive implantation. In this paper, the progress of injectable self-healing hydrogels is presented by combining developments in the fundamental knowledge of polymer designs and discussions on the practical biomedical applications of the materials. The mechanisms of different types of self-healing hydrogels are introduced first and their performances are then discussed, followed by a review of the self-healing hydrogels with injectability. The applications of the injectable self-healing hydrogels are discussed in the final section. Statement of Significance: This paper provides an overview of the progress of a smart material, injectable self-healing hydrogel, during the past ten years and mainly focuses on its recent development. This paper presents developments in the fundamental knowledge in polymer designs and discussions on the practical biomedical application of the materials, which sheds more light on the advancement of injectable self-healing hydrogels. This paper should be of interest to the readers who are curious about the advances of injectable self-healing hydrogels.